Flexor Digitorum Accessorius Longus: Importance of Posterior Ankle Endoscopy - Jorge Pablo Batista; Jorge Javier del Vecchio; Pau Golanó; Jordi Vega (Case Reports in Orthopedics)
Endoscopy for the posterior region of the ankle through two portals is becoming more widespread for the treatment of a large number of conditions which used to be treated with open surgery years ago. The tendon of the flexor hallucis longus (FHL) travels along an osteofibrous tunnel between the posterolateral and posteromedial tubercles of the talus. Chronic inflammation of this tendon may lead to painful stenosing tenosynovitis. The aim of this report is to describe two cases depicting an accessory tendon which is an anatomical variation of the flexor hallucis longus in patients with posterior friction syndrome due to posterior ankle impingement and associated with a posteromedial osteochondral lesion of the talus. The anatomical variation (FDAL) described was a finding during an endoscopy of the posterior region of the ankle, and we have spared it by sectioning the superior flexor retinaculum only. The accessory flexor digitorum longus is an anatomical variation and should be taken into account when performing an arthroscopy of the posterior region of the ankle. We recommend this treatment on this type of injury although we admit this does not make a definite conclusion.